2018
DOI: 10.31910/rudca.v21.n2.2018.968
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different substrates and auxins on rooting of Leucadendron sp. (Proteaceae)

Abstract: Colombian flower growers are faced with economic and social problems, so they are looking for alternatives, which include Proteas, ornamentals that require research that ensures an appropriate, local technical management. One of the Proteas most likely to be involved in this search is the genus Leucadendron. Therefore, this study aimed to establish the best basis for rooting its cuttings. The experimental design was a split plot design with a factorial arrangement. Four substrates were evaluated in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
3
0
2
Order By: Relevance
“…These results are in accordance with those obtained by Rajkumar et al (2016), Manila et al (2017) and Peña- Baracaldo et al (2018), who observed that vermiculite substrate was the best rooting medium in increasing the rooting percentage of many species cuttings than the other substrates. The main reasons in increasing the rooting percentage of C. erectus cuttings under vermiculite medium may be due to better aeration, excellent drainage, more water holding capacity and release of nutrients gradually from vermiculite medium resulting in better rooting percentages (Ansari, 2013;Manila et al, 2017).…”
Section: Rooting Percentagesupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in accordance with those obtained by Rajkumar et al (2016), Manila et al (2017) and Peña- Baracaldo et al (2018), who observed that vermiculite substrate was the best rooting medium in increasing the rooting percentage of many species cuttings than the other substrates. The main reasons in increasing the rooting percentage of C. erectus cuttings under vermiculite medium may be due to better aeration, excellent drainage, more water holding capacity and release of nutrients gradually from vermiculite medium resulting in better rooting percentages (Ansari, 2013;Manila et al, 2017).…”
Section: Rooting Percentagesupporting
confidence: 93%
“…However, the lowest root and vegetative characteristics were recorded with clay medium. Several investigations have shown that the use of vermiculite as rooting media resulted in a considerable increase in root and vegetative characteristics of cuttings Manila et al, 2017;Peña-Baracaldo et al, 2018). The positive effect of vermiculite substrate in increasing the root and shoot characteristics of cuttings may be attributed to its role on improving the soil aeration resulting in high water retention capacity and more availability of nutrients to roots (Rajkumar et al, 2017;Kumar et al, 2019).…”
Section: Root and Vegetative Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Además, esta técnica podría emplearse para la domesticación y conservación de especies medicinales (Feria-Arroyo et al, 2010;Duarte et al, 2018). Sin embargo, el proceso de enraizamiento de estacas está regulado por una combinación óptima de procesos fisiológicos (aspectos relacionados a la calidad, edad, tipo y estado fitosanitario de las estacas), condiciones ambientales (humedad del ambiente y características del sustrato), características genotipo de la planta madre y condiciones de propagación (Castillo-Flores et al, 2013;Peña-Baracaldo et al, 2018;Bannoud & Bellini, 2021). Entre las condiciones ambientales y de propagación que se pueden manipular con facilidad para hacer más eficiente el desarrollo de raíces adventicias se destacan la composición del sustrato, el tipo y dosis de hormona, que si no se emplean de manera apropiada pueden limitar altamente la obtención de rizogénesis adventicia.…”
Section: Introductionunclassified